Por la "quineación" de los qualia cartesianos - García-Carpintero, Manuel (Análisis Filosófico, 1999)
Dennett (1988) provides a much discussed argument against qualia, at least when conceived as philosophers (otherwise holding different views) like Block, Chalmers, Loar and Searle do. My goal in this paper is to vindicate Dennett’s argument, construed in a certain way. As 1 will present it, the argument supports the claim that qualia are constitutively representational. More specifically, against Block and Chalmers the argument supports the claim that the radical distinction between phenomenal and information-processing consciousness they draw does not exist; and against Loar and Searle, that qualia are constitutively representational in an externalist understanding of this.